2016
DOI: 10.18869/acadpub.ihepsaj.4.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Predication of Compliance to Standard Precautions among Nurses in Educational Hospitals inZahedan Based on Health Belief Model

Abstract: BaCkgRound and oBjeCtIVe:StandaRd pReCautIons aRe a pRopeR stRategy foR pReVentIon of oCCupatIonal dIseases among nuRses. The study was aImed to InVestIgate the applICatIon of StandaRd pReCautIons foR pReVentIon of tRansmIssIon of hepatItIs B and C and HIV In eduCatIonal hospItals. MateRIals and methods:In thIs CRoss-seCtIonal study 218 nuRses, 174 female and 44 male, of two eduCatIonal hospItals In Zahedan, IRan uses multI-stages samplIng method weRe studIed. A polyChotomy standaRd questIonnaIRe InCludIng dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…A significant negative association was also observed between perceived barriers and health motivation. This finding is consistent with that of Masoudi et al study [17] . In another study, demographic background, knowledge of COVID-19, HBM constructs explained 58.1% of the variance in behavioral intention among nursing students [18] .…”
Section: Journal Of Education and Community Healthsupporting
confidence: 94%
See 3 more Smart Citations
“…A significant negative association was also observed between perceived barriers and health motivation. This finding is consistent with that of Masoudi et al study [17] . In another study, demographic background, knowledge of COVID-19, HBM constructs explained 58.1% of the variance in behavioral intention among nursing students [18] .…”
Section: Journal Of Education and Community Healthsupporting
confidence: 94%
“…When not taken seriously, the threat of disease reduces people's motivation to take protective measures and their superficial assessment of the effectiveness of the recommended strategies. This finding was consistent with the results of some studies [17,26] . In the study of Tsai et al, there was a significant relationship between perceived susceptibility and perceived severity with behavioral intention to prevent COVID-19 [18] .…”
Section: Journal Of Education and Community Healthsupporting
confidence: 94%
See 2 more Smart Citations
“…study in Zahedan, which showed no significant relationship between performance and perceived benefits in relation to the prevention of hepatitis B and C and AIDS. [ 30 ] One of the reasons for such discrepancy might be differences in the study population, the type of educational intervention, and the educational method to present the subject matter, which result in an increase in perceived benefits in relation to the observation of SPs.…”
Section: Discussionmentioning
confidence: 99%